Implementasi Pembelajaran Matematika Berbasis E-learning Pada Penguatan Pendidikan Karakter (PPK) Pasca Era New Normal - Ririn Ikrimah; Darwan Darwan; Widodo Winarso (ITEJ (Information Technology Engineering Journals), 2022)
The existence of technological advances in the field of education does not rule out the possibility of negative things arising from the existence of e-learning. For students, the negative impact of based e-learningis a decrease in the affective or character aspects. Technological progress should be a bridge for the progress of the nation, in education to overcome the shift in character in students is to make e-learning a medium for character building. E-learning can be integrated with the implementation of strengthening character education programs (SCE). The program is implemented to reduce cases of moral degradation that are currently occurring among the community, especially teenagers, to optimize the use of technology in learning mathematics, and to implementation of SCE in based e-learning. This study uses a qualitative method with a case study approach. The instruments used are a self-assessment scale, peer rating scale, and interview guidelines for managing character education strengthening for students at SMPN 3 Plered. The results obtained are that most of the students (97%) have religious character values, honesty, responsibility, curiosity, discipline, independence, communicativeness, and tolerance. The obstacle experienced when implementation SCE in mathematics learning based e-learningis teachers and students lack of understanding and awareness regarding character education. Efforts made to minimize the obstacles experienced are to provide an understanding of character education for teachers and students, as well as provide direction to students who still do not have the awareness to instill character values in themselves.